Seismic responses of a long-span transmission tower and tower-line system. Issue 1 (1st October 2022) - Shen, Guohui; Yu, Hangcong; Yu, Liang; Li, Buhui; Yao, Jianfeng
Abstract : The seismic responses of a long-span transmission tower (LTT) and tower-line system (TL) are presented in the paper. The mode decomposition response spectrum method (MDR) and time domain analysis method (TD) are both employed to obtain the seismic responses. The axial stress of the main member of the tower and TL obtained using these two methods are compared. Results show that the first six vibration frequencies of the tower and TL are quite close. The axial stresses of main members under the TL condition undertake greater values than those under the tower condition. Based on the time analysis method, the axial stresses of the main member under the TL condition are much larger than those under the tower condition, indicating that the mass effect of the transmission line has a similar effect as tuned mass dampers in reducing the seismic response. For the TL, the MDR presents much larger values than those of the TD which may partially contribute to the fact that the coupling effect of the line and the tower cannot be well addressed by the mode decomposition method.